2014
DOI: 10.1002/bit.25471
|View full text |Cite
|
Sign up to set email alerts
|

Surface display of roGFP for monitoring redox status of extracellular microenvironments in Shewanella oneidensis biofilms

Abstract: Biofilms are the most ubiquitous and resilient form of microbial life on earth. One most important feature of a biofilm is the presence of a self-produced matrix, which creates highly heterogeneous and dynamic microenvironments within biofilms. Redox status in biofilm microenvironments plays a critical role in biofilm development and function. However, there is a lack of non-intrusive tools to quantify extracellular redox status of microenvironments within a biofilm matrix. In this study, using Shewanella onei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Moreover, Ca 2+ ‐binding proteins play an important role in bacterial surface adhesion as attachment factors (Porsch et al, ). In S. oneidensis , Ca 2+ ‐binding proteins have been reported to be involved in initial attachment, where the Ca 2+ stimulates auto aggregation of MR‐1 cells (Satchell, ; Sivakumar et al, ; Theunissen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Ca 2+ ‐binding proteins play an important role in bacterial surface adhesion as attachment factors (Porsch et al, ). In S. oneidensis , Ca 2+ ‐binding proteins have been reported to be involved in initial attachment, where the Ca 2+ stimulates auto aggregation of MR‐1 cells (Satchell, ; Sivakumar et al, ; Theunissen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Calcium regulates extracellular polymeric substance production during biofilm formation and development in many species (Patrauchan et al 2005;Sarkisova et al 2005), and calcium-binding proteins play important role in bacterial surface adhesion (Porsch et al 2013). Specifically, in S. oneidensis MR-1, calcium-binding proteins have been reported to be involved in initial attachment, and calcium stimulates autoaggregation of MR-1 cells significantly (Satchell 2011;Sivakumar et al 2015;Theunissen et al 2010). Hence, the positive relation between biofilm formation and calcium supply in substratum was as expected, indicating the practicability of this gradient generator flow chamber.…”
Section: Development Of Dual-species Biofilms Under Nitrate-gradientsmentioning
confidence: 99%
“…The bacterial strains, plasmids and primers used in the current study are shown in Table 6.1. The growth media and culture incubation conditions for bacterial growth in both planktonic and biofilm mode were described in detail previously (Ding et al 2014a;Sivakumar et al 2015). Unless otherwise stated, the bacterial cultures in planktonic growth mode were incubated under aerobic conditions in a rotary shaker (200 rpm) at 30 o C in LB medium or highly defined modified M1 minimal medium (MM1) with 20 mM lactate as the carbon source.…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
“…The composition of the MM1 medium was described in detail in Section 3.2.1 (Chapter 3) (Ding et al 2014a;Sivakumar et al 2015). For biofilm growth, diluted LB medium (10 × dilution) was used (Zhang et al 2014).…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation